Psychological factors in chronic odema: a case control study - Moffatt, Christine J.; Aubeeluck, Aimee; Doherty, Debra; Mortimer, Peter; Quere, Isabella (Mary Anne Liebert, 2017)
Objective: To examine psychological health and perceived social support in patients with chronic oedema (CO). Methods: A random sample of patients who had been previously identified with in a chronic oedema (CO) service in an urban area of south west London were group matched for age and gender with community controls in a case control study. Results: One hundred and seven cases and 102 controls (women 82%) were identified. CO was caused by cancer or its treatment in 51 (48%) of cases and affected the leg in 65 (61%); the arm 41(38%) and the limb and midline in 15 (14%). Length of time with CO was long with 50 (47%) suffering for > 10 years. Cases were more likely to be single or divorced/separated (p=0.041) and have reduced mobility (p <0.001). SF36 scores showed cases had significantly poorer overall HRQOL in particular: physical functioning (p=0.003); role physical (p<0.001) general health (p=0.026); vitality (p=0.015); social function (p=0.007) and role emotional (p=0.041). EQ5D health index scores were significantly reduced in cases by 13 points (P=<0.001, 95% CI 5.8, 21.6) compared with controls with a similar pattern for the VAS scale (p<0.00 95% CI 7.6, 17.1). The MOS scale showed cases had similar size social networks to the control group (5.8/6.6 p=0.49) but had lower total perceived social support scores (67.8/76.1 p=0.018). Cases had reduced support in all 5 domains with tangible and affectionate support significantly reduced for cases compared to controls. Cases used significantly fewer coping strategies (COPE scale) than controls with regard to: active coping (p=0.024); planning (p<0.001) and use of instrumental support (p=0.006). Significantly higher levels of coping were used by cases for the following domains: restraint (p=0.031), positive reinterpretation and growth (p<0.001); acceptance (<0.001); denial (p<0.001); mental disengagement (p<0.001); behavioural disengagement (<0.001): substance abuse (p=0.010) and humour (p<0.001). Conclusions: Patients with CO have poorer health and greater impact on many aspects of HRQOL. While the size of social networks they report appear preserved,the levels of perceived social support are reduced. The pattern of use of coping strategies was complex with evidence of reduced problem solving combined with enhanced emotion focused coping such as acceptance and reinterpretation indicating illness adjustment. Deficits in the ability to function socially combined with perceived reduction in support and reduced mental health and emotional scores within the SF36 scale indicate the risk of developing psychological issues such as depression. Systems of care should offer an environment to address these issues